Evaluation of Fast Mobility Particle Sizer (FMPS) for Ambient Aerosol Measurement - Yue Lin; Liem Pham; Xiaoliang Wang; Roya Bahreini; Heejung S. Jung (Aerosol and Air Quality Research)
Abstract Fast Mobility Particle Sizer (FMPS) size distribution measurements with different inversion matrices were compared with the Scanning Mobility Particle Sizer (SMPS) for ambient aerosols sampled from a background location in Riverside, CA in this study. The FMPS-compact matrix showed the best agreement with SMPS for particle concentration in the size ranges of 9–359 nm and 9–100 nm (for ultrafine particles). The FMPS-compact matrix also showed the best agreement with the SMPS for mode diameter. All FMPS inversion matrices showed size-dependent discrepancies compared with the SMPS. Measurement of the non-volatile fraction of ambient aerosol downstream of a catalytic stripper showed that the FMPS-compact matrix agreed best with the SMPS with the FMPS over SMPS linear regression slope of 0.99–1.00 for particle concentrations. This is likely due to the restructuring of soot during the removal of volatile coating. This study showed that the soot and compact matrices are insufficient for ambient aerosol measurement. Challenges remain for FMPS measurements when particle morphologies are not known a priori or when they are different from near spherical shape or aggregate structure.